2021
DOI: 10.3390/foods10010190
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds in Wild Nettle (Urtica dioica L.) Leaves and Stalks: Polyphenols and Pigments upon Seasonal and Habitat Variations

Abstract: This study evaluated the presence of bioactives in wild nettle leaves and stalks during the phenological stage and in the context of natural habitat diversity. Thus, wild nettle samples collected before flowering, during flowering and after flowering from 14 habitats situated in three different regions (continental, mountain and seaside) were analyzed for low molecular weight polyphenols, carotenoids and chlorophylls using UPLC-MS/MS and HPLC analysis, while the ORAC method was performed for the antioxidant ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 43 publications
(98 reference statements)
8
66
0
Order By: Relevance
“…The phenolic profile of obtained MAE and PLE extracts did not differ qualitatively, unlike with the CE extract, where some compounds (myricetin and caffeic acid) could not be detected. A detailed description of phenolic composition with accompanying identification pathways for compounds lacking reference standards of nettle leaves from the Croatia region was reported previously [7], and is in accordance with results of this study. A total of 27 phenolic compounds were identified, belonging to the classes of benzoic, cinnamic and other phenolic acids, flavonols, flavan-3-ols, flavones and coumarins (Figure 2).…”
Section: Comparison Of Different Extraction Techniques For the Isolation Of Nettle Leaves' Polyphenolssupporting
confidence: 90%
See 2 more Smart Citations
“…The phenolic profile of obtained MAE and PLE extracts did not differ qualitatively, unlike with the CE extract, where some compounds (myricetin and caffeic acid) could not be detected. A detailed description of phenolic composition with accompanying identification pathways for compounds lacking reference standards of nettle leaves from the Croatia region was reported previously [7], and is in accordance with results of this study. A total of 27 phenolic compounds were identified, belonging to the classes of benzoic, cinnamic and other phenolic acids, flavonols, flavan-3-ols, flavones and coumarins (Figure 2).…”
Section: Comparison Of Different Extraction Techniques For the Isolation Of Nettle Leaves' Polyphenolssupporting
confidence: 90%
“…Acetone suitability for extraction of plant polyphenols has been reported previously [23] and can be attributed to its ability to inhibit and/or break polyphenol-protein interactions and therefore prevent the formation of insoluble complex and consequently increase the polyphenolic yield [24]. According to Rezaie et al (2015) [25] acetone is suitable for the extraction of non-glycosidic polyphenols due to its poor ability to form hydrogen bonds, so its high effectiveness in extraction of nettle leaves polyphenols can be related to the predominance of phenolic acids and non-glycosylated flavonoid derivates in nettle polyphenolic profile [7]. Temperature was also shown to be a significant factor for the isolation of nettle leaves polyphenols during MAE.…”
Section: Optimization Of Mae Of Nettle Leaves' Polyphenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, the accumulation of color pigments varies with climate and habitat diversity. Plants grown in cold climates generally exhibit more antioxidant properties as a result of oxidative stress defense, while color pigment synthesis is increased due to exposure to higher temperatures and more sunlight (González‐Talice, Yuri, & del Pozo, 2013; Repajić et al, 2021; Saini, Nile, & Park, 2015). Besides all the stability of chlorophyll varied according to the subspecies of stinging nettle.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies reported that young nettle leaves extracts are a good source of polyphenols and phytochemicals that render them with nutritional, nutraceutical and functional properties. Polyphenols content of nettle leaves showed a decreasing trend with the phenological stage, total polyphenols decreased for almost 50% by the 3rd phenological stage (Repajić et al, 2021).…”
Section: Consumable Parts and Traditional Manipulation Practices To Collect Stinging Nettlementioning
confidence: 93%